2021
DOI: 10.3389/fpls.2021.779122
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Application of Emerging Technologies to Accelerate Crop Improvement – A Collaborative Pipeline to Introgress Herbicide Tolerance Into Chickpea

Abstract: Accelerating genetic gain in crop improvement is required to ensure improved yield and yield stability under increasingly challenging climatic conditions. This case study demonstrates the effective confluence of innovative breeding technologies within a collaborative breeding framework to develop and rapidly introgress imidazolinone Group 2 herbicide tolerance into an adapted Australian chickpea genetic background. A well-adapted, high-yielding desi cultivar PBA HatTrick was treated with ethyl methanesulfonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Applications of SB include the development of biparental and more complex mapping populations, pyramiding traits, hastening backcrosses, phenotyping adult plant traits, mutant studies, and genetic transformation experiments [ 7 , 29 ]. Recent research has shown the power of combining emerging techniques, such as gene editing, high-throughput phenotyping and genotyping, genomic selection (GS), and MAS, with SB for accelerating crop improvement [ 30 , 40 , 42 , 43 , 44 , 45 , 46 ]. Furthermore, the cost and space requirements for producing a large number of inbred lines can be minimized by planting them at high plant densities [ 47 ].…”
Section: Sb Applications In Research and Breedingmentioning
confidence: 99%
See 3 more Smart Citations
“…Applications of SB include the development of biparental and more complex mapping populations, pyramiding traits, hastening backcrosses, phenotyping adult plant traits, mutant studies, and genetic transformation experiments [ 7 , 29 ]. Recent research has shown the power of combining emerging techniques, such as gene editing, high-throughput phenotyping and genotyping, genomic selection (GS), and MAS, with SB for accelerating crop improvement [ 30 , 40 , 42 , 43 , 44 , 45 , 46 ]. Furthermore, the cost and space requirements for producing a large number of inbred lines can be minimized by planting them at high plant densities [ 47 ].…”
Section: Sb Applications In Research and Breedingmentioning
confidence: 99%
“…Since 2016, SB has been integrated within all cool-season legume public breeding programs in Australia, with more than 45,000 individuals processed through an aSSD platform at the University of Western Australia. The resulting RILs have been used for gene-trait associations [ 43 , 44 , 45 , 46 ], and SB has been integrated with other technologies to accelerate cultivar development pipelines [ 40 ].…”
Section: Model Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, novel genetic variation can be induced using chemical mutagenesis to create mutant populations, in turn producing new allelic variants and/or discovering new modes of action for weed control. Implementation of this method can be seen where imidazolidinone tolerance in wheat ( Newhouse et al, 1992 ) and chickpea ( Croser et al, 2021 ) was produced using ethyl methanesulfonate (EMS) mutant population. Leucaena leucocephala is another example of the implementation of chemical mutagenesis for weed management.…”
Section: Potential Molecular Approaches Targeting Weeds To Control Fi...mentioning
confidence: 99%